FEASIBILITY OF BUSINESS PORANG (Amorphophallus muelleri. Blum) IN EAST LOMBOK DISTRICT - Dwi Haryati Ningsih; Rini Endang Prasetyowati; Muhamad Sarlan (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
The purpose of this study was to examine the feasibility of porang farming in East Lombok Regency. Improvements in the cultivation system, technology and downstreaming of porang farming are expected to increase porang productivity which in turn increases farmers' income. Research activities are carried out in several stages, including: (i) site survey, identifying problems, and preparing proposals; (ii) data collection, data tabulation, and data analysis; (iii) draw conclusions and recommend the results of the study. The recommendations generated from this research are in the form of information related to the financial value obtained by porang farmers in East Lombok Regency. Based on the results of the study, it can be seen that the income obtained in porang farming is Rp. 39,696,316/LLG and Rp. 198.481. 580/hectare. And based on the calculation of the B/C ratio of porang farming in East Lombok Regency, the B/C ratio value 1 is 5.3. This shows that porang farming in East Lombok Regency is feasible.